Prostate Cancer Characteristics in Renal Transplant Recipients: A 25-Year Experience From a Single Centre - Spatafora, Pietro; Sessa, Francesco; Caroassai Grisanti, Simone; Bisegna, Claudio; Saieva, Calogero; Roviello, Giandomenico; Polverino, Paolo; Rivetti, Anna; Verdelli, Lorenzo; Zanazzi, Maria; Beatrice, Detti; Vignolini, Graziano; et al. (Frontiers in Surgery, 2021)
Objectives: The incidence of prostate cancer in renal transplant recipients (RTRs) is increasing, but few data are available in the literature. In this study, we reviewed the 25-year experience in the management of prostate cancer after kidney transplantation at the Florence Transplant Centre. Methods: We retrospectively reviewed the data from 617 RTR male patients who underwent renal transplantation at our institute between July 1996 and September 2016. Data regarding demographics, renal transplantation, prostate cancer and immunosuppressive treatment were analysed. The probability of death was estimated by using the Kaplan-Meier method and differences between patients’ groups were assessed by the log-rank test. Results: From July 1991 to September 2016, 617 kidney transplantations of male patients were performed at our institute. Among these, 20 patients were subsequently diagnosed with prostate cancer accounting for a cumulative incidence of 3.24%. After a median follow-up of 59 months, ten patients underwent radical prostatectomy whereas ten patients underwent primary radiotherapy. A biochemical recurrence was identified in 5 (25%) patients while a fatal event occurred in 11 (55%) patients. Univariate Cox regression showed that the basal value of PSA >10 ng/mL was the only significant factor negatively affecting the survival of patients. Conclusions: Standard treatments can be proposed to RTR with satisfactory results on both postoperative and oncological outcomes. Further studies are needed to address the issue of prostate cancer screening based on PSA levels and the optimal management of prostate cancer in RTRs.